Seasonal trend analysis and influence of meteorological factors on the concentration of atmospheric pollutants in an urban area - Naresh Kumar; Priya Ranjan; Suman . (Journal of Air Pollution and Health)
Introduction: Air pollution is a growing concern in Greater Noida, Uttar Pradesh, where meteorological factors play a major role. As urbanization accelerates, the region has not yet thoroughly examined the impact of factors like temperature, humidity, wind direction, and speed on pollutants like Particulate Matters (PM2.5, PM10), Nitrogen dioxide (NO2), and Sulfur dioxide (SO2). Materials and methods: To explore this issue, a 12-month study (January to December 2023) was conducted to analyze the relationships between these meteorological factors and pollutant levels. In the present study, pollutant movement was tracked over time. Pearson correlation was used to correlate air pollution concentrations with weather conditions. Results: The study revealed that the average concentrations of PM10, PM2.5, and NO2 were 912.54 µg/m³, 257.42 µg/m³, and 65.98 µg/m³, respectively. In contrast, SO2 had an average concentration of 26.85 µg/m³. Conclusion: The study indicates that particulate matter and temperature are strongly negatively correlated, while wind speed shows a weak positive correlation with particulate matter. Pollution levels and relative humidity also display a negative correlation, as do particulate matter concentrations and humidity. However, gaseous pollutants exhibit little to no significant correlation with these weather conditions.